ORGANIZATION OF SCIENTIFIC AND RESEARCH ACLIVITIES OF STUDENTS IN THE CONTEXT OF SCIENTIFIC AND SUBJECT FOREIGN LANGUAGE TRAINING - Pavliuk, Roman O. (Educological discourse, 2016)
The modern approaches to the organization of research activities of students in the context of scientific and subject foreign language training are opened in the article. The views and approaches of modern Ukrainian scientists to designing of the system of research activities of students are analyzed. Current ideas of scientists on the development of pedagogical conditions of organization of research activities are suggested. It is identified the advantages and disadvantages in the common approaches to organization of pedagogical conditions for research activity of students in the context of scientific and subject foreign language training.